2009
DOI: 10.1002/jcb.22120
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis in mouse calvarial osteoblasts highlights sets of genes regulated by modeled microgravity and identifies a “mechanoresponsive osteoblast gene signature”

Abstract: Mechanical unloading is known to be detrimental for the skeleton, but the underlying molecular mechanisms are not fully elucidated. We performed global transcriptome analysis of mouse calvarial osteoblasts grown for 5 days at unit gravity (1g) or under modeled microgravity (0.008g) in the NASA-developed rotating wall vessel (RWV) bioreactor. Elaboration of gene profiling data evidenced that, among the >20,000 gene probes evaluated, 45 genes were significantly up-regulated (cut-off >2) and 88 were down-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 49 publications
5
65
1
Order By: Relevance
“…CXCL10 not only impacts thymic migration of T cells, but the altered expression of CXCL10 due to spaceflight also relates back to the changes in expression that we observed in the GR heterocomplex and stress-related genes. Recent work has suggested that CXCL10 is down-regulated in splenic mRNA due to stress via restraint [Curtin et al, 2009], as well as in the mRNA of T cells and osteoblasts cultured in a vector less gravity bioreactor [HughesFulford et al, 2005;Capulli et al, 2009]. Similar to many of the previously mentioned genes that were found to be altered by spaceflight, this down-regulation observed in times of stress most likely occurs due to changes in STAT1 and the NF-kB pathway.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…CXCL10 not only impacts thymic migration of T cells, but the altered expression of CXCL10 due to spaceflight also relates back to the changes in expression that we observed in the GR heterocomplex and stress-related genes. Recent work has suggested that CXCL10 is down-regulated in splenic mRNA due to stress via restraint [Curtin et al, 2009], as well as in the mRNA of T cells and osteoblasts cultured in a vector less gravity bioreactor [HughesFulford et al, 2005;Capulli et al, 2009]. Similar to many of the previously mentioned genes that were found to be altered by spaceflight, this down-regulation observed in times of stress most likely occurs due to changes in STAT1 and the NF-kB pathway.…”
Section: Discussionmentioning
confidence: 77%
“…With these data in mind, the question arises as to the cause of this signal dampening effect, which ultimately results in the loss of DP T cells. Microarray studies have been used by others to examine changes in gene expression in space flown tissues such as liver, T cells, osteoblasts, renal cells, and muscle cells [Hammond et al, 2000;Allen et al, 2009;Baqai et al, 2009;Capulli et al, 2009]. For example, a cDNA microarray of leukemic T cells flown in space for 24 h revealed an 11.7-fold increase of a tumor suppressor gene [Lewis et al, 2001].…”
mentioning
confidence: 98%
“…These cytoskeletal changes are responsible for cellular adaptations to different surfaces. [Color figure can be seen in the online version of this article, available at http://wileyonlinelibrary.com/bit] and differentiation (Capulli et al, 2009), there are currently no reliable experimental tools for quantifying the distribution and modulation of signaling protein networks amongst subcellular structures during these events. This situation is complicated by the fact that a given signaling protein may be involved in more than one intracellular response or pathway, e.g., signal transduction, metabolic, and catalytic functions, and mechanical support.…”
Section: Kinome Profiling Of Cells On Pepchip Kinase Peptide Microarrmentioning
confidence: 99%
“…Out of the seven microarray studies involving bone cells, five studies have the gene lists published in the paper or supplemental tables. Since the majority (four out of five) were studies done in mice (Pardo et al, 2005;Patel et al, 2007;Capulli et al, 2009;Sambandam et al 2010) and one was in human (Qian et al, 2007), I chose to use those four gene lists to compile into one master list in the same format, and uploaded them to the DAVID Functional Annotation tool for pathway analysis. The list was run as species Mouse and Identified the statistically significant KEGG Pathways (data not shown).…”
Section: Sambandam Et Almentioning
confidence: 99%
“…. The highest overlapped (in three of the five studies) genes were osteoglycin(OGN), osteomodulin (OMD), and secreted Frizzle-Related Protein 2 (SFRP2) and all three genes were down-regulated in all the microarray/microgravity studies that identified them (Pardo et al, 2005;Patel et al, 2007;Capulli et al, 2009). Osteoglycin(OGN) encodes a protein (a small proteoglycan) which induces bone formation in conjunction with transforming growth factor beta.…”
Section: Sambandam Et Almentioning
confidence: 99%